134 Neonatalsepsis: current information and how we are doing?. (11th October 2021) - Quinn, Shauna; Kilgarrif, Daithi; Friesen, Noel
Abstract : Early neonatal sepsis is defined as sepsis within the first 7 days of life. There is an incidence of 0.1-1.2/1000 live births, with variation between populations. A significant reduction in GBS sepsis is recognised with introduction of intrapartum antibiotics. Predisposing risk factors include PROM, history of GBS sepsis, chorioamnionitis, prematurity and inadequate intrapartum antibiotics. The aim of this audit is to compare adequate and inadequate treatment of GBS +ve and PROM mothers and subsequent neonatal outcomes with consideration of the EOS risk calculator. The study cohort consists of 114 neonates born at St John of God Midland between January and March. It is a retrospective review of all neonates screened during this period, with clinical data and results from Australian Clinical Labs, Infomedix and iSoft. Of all 114 neonates screened, all were screened with a CRP and 68 with additional blood cultures. Results demonstrated one positive blood culture for S. Epidermidis, one sepsis with chorio positive growth and two presumed cases of chorioamnionitis with no growth. 50% of those screened were treated until Mid-February, where-after there was an increase noted likely secondary to medical changeover. Amongst those screened, 66% were empirically treated and 24% treated following a CRP rise. We identified an issue regarding insufficient antepartum antibiotics (<4 hours). 32% of mothers were GBS+ve but only 8% received adequate antibiotics and 24% were treated inadequately. Similarly, in PROM >18 hours only 44% received adequate treatment despite inpatient management for > 4 hours prior to birth. All 15 neonates born to inadequately treated mothers, were screened, two treated for CRP rises and two treated for additional risk factors. This review highlights the importance of documentation, with inclusion of rupture of membrane and antibiotic administration times, gathering data required for the EOS calculator and liaising with the obstetric team to ensure timely administration of antibiotics. We can reduce screening and treating of neonates by optimising antepartum management or use of the EOS calculator.